Uruguay : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that the Uruguayan economy continues to decelerate gradually. Real GDP growth is estimated to have softened to a still robust 3.25 percent in 2014 from 4.5 percent in 2013, mostly reflecting the moderation in domestic demand growth amid a less favorable external environment. Weak economic conditions abroad have continued to weigh on Uruguay's current account, particularly on the services side. Economic activity is projected to decelerate further but remain solid. The pass-through of lower global oil prices to end-user prices will be gradual, as part of the windfall from lower oil prices will initially be used to shore up the operating balance of the state-owned petroleum enterprise.